Aplikasi Teknologi Pengolahan Frozen Fishcake Berbasis Hasil Perikanan Air Tawar dan Jamur Sawit - Nur'aini, Hesti; Andriani, Evi; Fariadi, Herri; Syahputra, Yudian; Arsi, Yeji Loni; Raju, Raju (Jurnal Gotong Royong, 2026)
Kungkai Baru Village has high potential in fishery and palm mushroom production, which can be developed into high-value food products. Community service activities have been carried out to increase the knowledge and skills of the Kungkai Baru Village community regarding the potential of catfish and palm mushrooms. The activities were carried out through socialization and practical training on fishcake processing based on catfish and palm mushrooms, followed by packaging and labeling practices. The results of the activities showed an increase in the knowledge and skills of the Kungkai Baru Village community, especially in fishcake processing technology, with the hope that it can be used as a mainstay product and thus improve the village economy.